Falsche Freundschaft oder interferenzfehler slowenischer Deutschlernender aus dem Englischen - Leskovec, Mojca (Vestnik za tuje jezike, 2019)
The discovery, postulated in the Common European Framework of Reference for Languages, that there is only one communicative competence, to which all knowledge and experience of language contribute and in which languages interrelate and interact, manifests itself amongst other things in the plurilingual orientation as one of the many didactic-methodological principles of the post-method era. According to this, it is recommended to take advantage of the knowledge of other languages when learning a new language. The languages one has learned, however, can affect the learning of a further language in a positive as well as a negative way. The aim of this article is to show the interferences of English as the first foreign language on the example of Slovene learners of German as a second foreign language in a secondary school, and to discuss how to integrate them in the language classroom so that the learning process would be more effective and efficient. The article presents interferences that the author collected in her years teaching at secondary school. Most of them are semantic, although morphological and orthographic interferences could also be found.
Keywords: angleščina; didaktika jezika; interferenca; nemščina; raznojezičnost; sporazumevalna zmožnost; transfer; tuji jeziki